Methods in membrane biology : Volume 4, biophysical approaches - Korn, Edward D. (Plenum Press, 1975)
All membrane biologist would agree that a major element of all biology membrane is a bilayer of phodpholipids which, in some instances, also contains other lipids, notably sterols and glycolipids.